2023
DOI: 10.1101/2023.01.26.525727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single fluorogen imaging reveals distinct environmental and structural features of biomolecular condensates

Abstract: Recent investigations have suggested that biomolecular condensates are viscoelastic materials. This implies that material properties of condensates are governed by internal microstructures. Furthermore, computations show that the internal organization in protein condensates is spatially inhomogeneous, featuring hub-and-spoke-like percolated networks of molecules. Here, we test these predictions using imaging of single fluorogenic dyes that are turned-on in response to specific chemical microenvironments. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 98 publications
2
32
0
Order By: Relevance
“…Recent coarsegrained simulations reproduced the measured phase behaviors for thirty variants of A1-LCD 13 , the PLCD derived from the RNA binding protein hnRNP A1. These computations and recent single fluorogen imaging studies 18 have shown that PLCDs within condensates form physically crosslinked networks with hub-and-spoke like topological structures. Hubs are organized around intermolecular crosslinks among clusters of aromatic stickers 18 .…”
mentioning
confidence: 69%
“…Recent coarsegrained simulations reproduced the measured phase behaviors for thirty variants of A1-LCD 13 , the PLCD derived from the RNA binding protein hnRNP A1. These computations and recent single fluorogen imaging studies 18 have shown that PLCDs within condensates form physically crosslinked networks with hub-and-spoke like topological structures. Hubs are organized around intermolecular crosslinks among clusters of aromatic stickers 18 .…”
mentioning
confidence: 69%
“…196 The sponge-like structures observed by Gall and colleagues for nucleoli and Cajal bodies 117 are evident even for the simplest of condensates, both computationally 3 and experimentally. 196…”
Section: Associative Macromolecules Form Prepercolation Clusters In S...mentioning
confidence: 95%
“…A useful starting point is the copious literature on partitioning of solutes and the considerations of solvent nonidealities in aqueous two-phase systems . The recent work of Wu et al shows that the interiors of condensates formed by intrinsically disordered low complexity domains are more hydrophobic than the coexisting dilute phases. Further, there are hotspots within interiors that are more hydrophobic than the background of condensates, suggesting that one cannot assume that molecules partitioning into condensates are crossing a boundary into materials of uniform hydrophobicity .…”
Section: Interfaces and Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations